An iPad-Based Tool for Improving the Skills of Children with Attention Deficit Disorder - Wrońska, Natalia (Int J Environ Res Public Health, 2015)
Attention Deficit Hyperactivity Disorder (ADHD), with a worldwide prevalence of 5.29%–7.1%, is one of the most common neurodevelopmental disorders among children and adolescents. Apart from typical symptoms like inattention, hyperactivity and impulsiveness, patients also evidence attention deficit problems with reading comprehension. This in turn causes poor school performance and widens the gap with peers without ADHD. This paper presents a novel and interactive tool based on Serious Games for Health, whose aim is not only to improve comprehension, but also hold the user’s attention. This tool is geared towards assessing reading quality and is intended for iPad devices. Preliminary results obtained from the experiment performed to evaluate the game are included in this report. A group of six typically developing children from Colegio Vizcaya aged between 8 and 12 took part in the evaluation of motivation, satisfaction and usability of the same therapy in the new media. Results obtained by participants playing the game were analysed together with questionnaires concerning the usability of the system. Game evaluation resulted in relatively good statistics-average score was 3 points out of 4 and average time for completing the exercise was 59 seconds. A SUS questionnaire with an average score of 92.75 out of 100 indicates that the game presented is user-friendly and an effective tool. Moreover, based on the feedback obtained from participants, the game had been improved and additional functionality introduced. Older participants completed the first game faster than the younger ones, but age was not influential in subsequent games.